Lamin A/C-dependent chromatin architecture safeguards naïve pluripotency to prevent aberrant cardiovascular cell fate and function - Wang, Yinuo; Elsherbiny, Adel; Kessler, Linda; Cordero, Julio; Shi, Haojie; Serke, Heike; Lityagina, Olga; Trogisch, Felix; Malek Mohammadi, Mona; El-Battrawy, Ibrahim; Backs, Johannes; Wieland, Thomas; et al. (Nature Communications, 2022)
Tight control of cell fate choices is crucial for normal development. Here we show that lamin A/C plays a key role in chromatin organization in embryonic stem cells (ESCs), which safeguards naïve pluripotency and ensures proper cell fate choices during cardiogenesis. We report changes in chromatin compaction and localization of cardiac genes in Lmna−/− ESCs resulting in precocious activation of a transcriptional program promoting cardiomyocyte versus endothelial cell fate. This is accompanied by premature cardiomyocyte differentiation, cell cycle withdrawal and abnormal contractility. Gata4 is activated by lamin A/C loss and Gata4 silencing or haploinsufficiency rescues the aberrant cardiovascular cell fate choices induced by lamin A/C deficiency. We uncover divergent functions of lamin A/C in naïve pluripotent stem cells and cardiomyocytes, which have distinct contributions to the transcriptional alterations of patients with LMNA-associated cardiomyopathy. We conclude that disruption of lamin A/C-dependent chromatin architecture in ESCs is a primary event in LMNA loss-of-function cardiomyopathy.
Gesehen am 18.01.2023